Frontal Suspension Procedure using Frontalis Muscle for Management of Ptosis - Soedjana, Hardisiswo (Jurnal Plastik Rekonstruksi, 2013)
Background : Ptosis has a reputation as a cosmetic problem, but it is more often as a functional deficit that can have real impact on patients’ lives. Ptosis results from the dysfunction of one or both of the upper eyelid retractors and often blocks peripheral vision. Ptosis can be congenital or caused by aging. Frontal suspension is one of few techniques for correction of ptosis especially for severe ptosis. Patient and Method : We reported one case of severe ptosis. The patient had bilateral congenital ptosis at both of upper eyelids. The upperlid excursion was 4 mm and marginal reflex distance (MRD) was 2 mm. A frontal suspension procedure using frontalis muscle was done for correction. Result : After frontal suspension procedure, MRDare 5 mm for both eyes. There wee no difficulty for closing the eyes. The cosmetic appearance was good. Patient was satisfied with the result. Conclusion : Frontal suspension procedure using frontalis muscle gives a good function and cosmetic result for severe ptosis.